The influence of public-private partnership on sustainable development in local authorities in Poland - Magdalena Kisała (Economic and Environmental Studies (E&ES), 2019)
The subject of the article is deliberations on the impact of public-private partnership on the implementation of the principle of sustainable development in local government units. The legislator imposes the obligation to perform public tasks on the local government units. They include duties that fall into the category of spatial and ecological order. The statutory obligation results in the necessity to undertake activities dependent on the currently binding law on the one hand, and on the capabilities and needs of a specific local government unit on the other hand. The potential of the local government unit determines the scope and speed of changes. Public-private partnership, as a form of cooperation between a public entity and a private partner, allows a division of tasks and risks between the parties, and thus uses the potential of a private partner and relieves the public body in the field of activities taken over by the private partner. Cooperation in performing public tasks allows to implement the assumptions of sustainable development based on the cooperation of socio-economic and ecological solutions, also in relation to the quality and economic conditions.
Keywords: K23; K32; 330; sustainable development; public private partnership; cooperation; local government